2009
DOI: 10.1007/s00330-009-1655-4
|View full text |Cite
|
Sign up to set email alerts
|

Aortic stiffness is associated with cardiac function and cerebral small vessel disease in patients with type 1 diabetes mellitus: assessment by magnetic resonance imaging

Abstract: ObjectiveTo evaluate, with the use of magnetic resonance imaging (MRI), whether aortic pulse wave velocity (PWV) is associated with cardiac left ventricular (LV) function and mass as well as with cerebral small vessel disease in patients with type 1 diabetes mellitus (DM).Materials and methodsWe included 86 consecutive type 1 DM patients (49 male, mean age 46.9 ± 11.7 years) in a prospective, cross-sectional study. Exclusion criteria included aortic/heart disease and general MRI contra-indications. MRI of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
56
2
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 34 publications
7
56
2
3
Order By: Relevance
“…19,28,[30][31][32] Our results lend further support to an association of large-artery stiffness with WMH burden, and extend the findings to markers of carotid stiffness, additionally demonstrating that this association is at least in part independent of carotid atherosclerosis. Markers of carotid stiffness were not associated with LIs in our sample, suggesting that carotid stiffness may have an important role in chronic hypoperfusion but not complete infarction in the territory of small arteries.…”
Section: Methods Population and Study Design The 3c-dijonsupporting
confidence: 79%
See 1 more Smart Citation
“…19,28,[30][31][32] Our results lend further support to an association of large-artery stiffness with WMH burden, and extend the findings to markers of carotid stiffness, additionally demonstrating that this association is at least in part independent of carotid atherosclerosis. Markers of carotid stiffness were not associated with LIs in our sample, suggesting that carotid stiffness may have an important role in chronic hypoperfusion but not complete infarction in the territory of small arteries.…”
Section: Methods Population and Study Design The 3c-dijonsupporting
confidence: 79%
“…The relationship of pulse wave velocity, a marker of aortic stiffness, with MRI markers of ischemic brain injury was recently assessed, in relatively small samples. 19,[28][29][30][31][32] After accounting for vascular risk factors, pulse wave velocity was consistently associated with WMH burden, [30][31][32] Abbreviations: CCA-IMT 5 common carotid artery intima-media thickness; CI 5 confidence interval; L-WMHV 5 large white matter hyperintensity volume (age-specific top quartile); OR 5 odds ratio (per SD increase); SE 5 standard error; SVD 5 small-vessel disease; WMHV 5 white matter hyperintensity volume. a Log-transformed ratio of WMHV over total white matter volume.…”
Section: Methods Population and Study Design The 3c-dijonmentioning
confidence: 99%
“…In addition, it maintains the blood supply to the heart (ie, the coronary circulation) and other organs during diastole. Numerous reports have used VE MRI to assess the aortic PWV (8,(13)(14)(15)(20)(21)(22), almost exclusively using the transit-time method with one-directional through-plane velocity-encoding at multiple sites perpendicular to the aorta. Rogers et al (28), Yu et al (29), and Fielden et al (30) assessed PWV from in-plane VE MRI acquisitions.…”
Section: Discussionmentioning
confidence: 99%
“…Multisite one-directional through-plane velocityencoded (VE) magnetic resonance imaging (MRI) has been applied for PWV assessment by calculating the speed of the flow wave or the velocity wave propagating through the aorta from the distance between measurement sites and the difference in time (ie, the transit time) of the arrival of the wave front at the respective sites (8,(13)(14)(15)(20)(21)(22). The 3D nature of MRI enables an accurate determination of the aortic length without restrictions regarding imaging planes.…”
mentioning
confidence: 99%
“…12 Also, stiffness of the large arteries may impair cerebral autoregulation, predisposing to hypoperfusion during hypotension, subsequently leading to ischemia. 13 Several cross-sectional studies relating arterial stiffness to the subclinical markers of dementia showed a relation between increased arterial stiffness and larger white matter lesion (WML) volumes, [14][15][16][17][18][19][20] more lacunar infarcts, 14,20,21 more brain atrophy, 12,20 and lower cerebral perfusion. 22 However, it is unknown whether arterial stiffness contributes to an increased development of ischemic and degenerative brain changes over time.…”
mentioning
confidence: 99%